A Three-Wave Longitudinal Study of Moderated Mediation Between High-Performance Work Systems and Employee Job Satisfaction: The Role of Relational Coordination and Peer Justice Climate - Haider, Sajid; De-Pablos-Heredero, Carmen; De-Pablos-Heredero, Monica (Frontiers in Psychology, 2020)
Existing literature lacks studies that examine the indirect effect of high performance work systems (HPWS) on employee job satisfaction through employee-employee relations. Moreover, less is known about the boundary conditions of this indirect effect. This study sought to longitudinally examine the mediating role of a specific form of employee-employee relations—relational coordination—in the relationship between HPWS and job satisfaction. Data were collected in three waves from the employees of commercial banks (N = 322). Partial least squares structural equation modeling (PLS-SEM) was used for data analysis. Results from multiple linear autoregressive longitudinal analysis indicate that HPWS predict relational coordination, which in turn partially mediates the HPWS-job satisfaction relationship. Perceptions of peer justice climate provide boundary conditions for the above mentioned mediating effect. This study contributes to existing literature by explaining moderated-mediation mechanisms through which HPWS predict employee job satisfaction. Managers can strengthen the effect of HPWS on employee-employee relations and subsequent effect on employee job satisfaction by promoting peer justice climate in organizations.